New АСС/AHA and ESC/ESH arterial hypertension guidelines - E. V. Reznik; I. G. Nikitin (Кардиоваскулярная терапия и профилактика)
The American College of Cardiology and the American Heart Association updated the guideline for the prevention, detection, evaluation and management of high blood pressure in adults in 2017 The European Society of Cardiology and the European Society оf Hypertension updated guidelines for the management of arterial hypertension in 2018. This article reviews new positions of these documents, compares approaches to current issues of managing of the patients with arterial hypertension, pro and contra with previous versions of similar documents. It is necessary to update the National guidelines for management of patients with arterial hypertension, which should include the dignity of both European and American approaches.